1940
DOI: 10.1021/ie50371a023
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Dielectrics Electrical and Physical Properties of Systems Containing Sparingly Soluble Oxidation Products in Liquid Paraffin

Abstract: To determine the significance of fluorescence and similar phenomena upon the optical measurements, solutions of different concentrations of Shell sample 100 in Nujol were made, and their optical densities (log 1/T) were measured on the Hardy spectrophotometer. The results showed that the oils obeyed Beer's law.Further work in which the transmission curves are being expressed by an equation is being carried on to provide constants that are a function of the color of the oils. In this manner it is hoped that a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1942
1942
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The solution containing 2.7 per cent thianthrene crystallized upon cooling to 20 °C., but the resulting power factor values did not materially change as the system became heterogeneous. The fact that the systems containing thiophenol remained homogeneous and had low power factors at the higher concentrations and lower temperatures used is in contrast with the phenolcontaining systems previously studied (11), which upon cooling formed emulsions that had high power factors.…”
Section: = Sulfur Compoundsmentioning
confidence: 69%
See 2 more Smart Citations
“…The solution containing 2.7 per cent thianthrene crystallized upon cooling to 20 °C., but the resulting power factor values did not materially change as the system became heterogeneous. The fact that the systems containing thiophenol remained homogeneous and had low power factors at the higher concentrations and lower temperatures used is in contrast with the phenolcontaining systems previously studied (11), which upon cooling formed emulsions that had high power factors.…”
Section: = Sulfur Compoundsmentioning
confidence: 69%
“…Inasmuch as all the systems with higher power factors than solutions containing equimolecular proportions of acid or base became heterogeneous upon cooling (whereupon their power factors increased), an alternative explanation seems possible. Previous work with soaps (8) and with oxidation products (11) showed that systems appearing to be homogeneous but becoming visually heterogeneous at lower temperatures often exhibit dielectric behaviors resembling those of heterogeneous rather than of homogeneous systems. Tri-n-butylamine From consideration of the data obtained it is believed that, although the presence of sufficiently high proportions of soluble salts resulting from reaction between nitrogen bases and carboxylic acids can cause high power factors in insulating oils, the presence of such compounds in proportions equivalent to the low nitrogen content of insulating oils does not appreciably affect the power factors of the solutions.…”
Section: Organic Salts Of Nitrogen Basesmentioning
confidence: 99%
See 1 more Smart Citation